THE HYDROCARBON LOSSES ON OIL CONTAMINATED SOIL BY LANDFARMING BIOREMEDIATION: A LABORATORY STUDY - M. Udiharto; Agus Yusuf; Syafrizal Syafrizal (Scientific Contributions Oil and Gas, 2000)
Bioremediation, as a relatively new technology, is expected to be able to remediate the hydrocarbon contaminated soils which are often found in almost all areas of the petroleum industries activities. The bioremediation experiment had been conducted in a laboratory scale. The oil uncontaminated soil and parafinic oil samples are taken from an oil field. The soil is mixed with more than 5% hydrocarbon concentration in order to obtain an artificial oil contaminated soil. Indigenous microorganisms can grow on this oil contaminated soil. During incubation times, microbial cells grow rapidly, then followed by drastic decline of hydrocarbon contents on soils. It indicates that the indigenous microorganisms are capable to degrade petroleum hydrocarbon. On the addition of the organic fertilizer treatment, the highest degradation of hydrocarbon occurs. During four months of treatment, the hydrocarbon content on soil decreases more than 54%.